Analisis Kinerja Mesin CNC Turning SL 25 Mori Seiki Ditinjau dari Nilai Kebulatan Benda Kerja di Bengkel Mekanik Polman Babel - Widian, Andri; Oktriadi, Yudi; Subkhan, Subkhan (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
In production machining process is something that must be prioritized. One factor that affects the quality of production is the condition of the machine tool. The Mori Seiki SL 25 CNC Turning Machine is a machine that has existed since 1998 at the Polman Babel Mechanic Workshop and has been used for production processes and learning facilities for approximately 25 years. The use of machine tools at that time can affect the machine's geometric conditions, affecting the quality of the product produced. Roundness is one of these geometric conditions because many components with round cross-sections affect the components' function if deviations occur. Deviations in the roundness value on the machine can be known by testing the roundness value of the machining workpiece. From these tests, geometric errors in the machine and the feasibility of the machine in processing workpieces at specific size tolerances can be seen. The workpiece resulting from the machining process will be measured for its roundness value and then analyzed using the Minimum Zone Center (MZC) method. The test results on the geometric conditions of the machine are that the highest roundness deviation is at position 1 with an average of 21.7 μm which is the outermost position of the clamping area. The slightest deviation value is at position 6 with an average of 10.9 μm, and the machine can produce workpieces with a tolerance above 21 μm.